INTERACTIVE E-MODULES ASSISTED BY GOOGLE SITES IN EFL: ITS EFFECT ON STUDENTS' CRITICAL THINKING AND LEARNING ENGAGEMENT - Kadek Ratnawati; Ni Luh Putu Artini; I Putu Indra Kusuma (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) Universitas PGRI Mahadewa Indonesia, 2024)
This study explores how interactive e-modules utilizing Google Sites affect high school students' critical thinking and involvement in EFL classrooms. Using a mixed-methods approach, it compares an experimental group utilizing e-modules to a control group that uses textbooks. The results revealed considerable gains in critical thinking and engagement in the experimental group. Qualitative evidence showed that these students were more engaged and collaborative. The study indicates that interactive e-modules may assist in creating a more dynamic learning environment, and it recommends integrating them into teaching techniques and investing in appropriate technology. Future studies ought to investigate the long-term impacts of these instruments.